Sustainability Report, Intellectual Capital dan Nilai Perusahaan - Yulistia M, Resti; Frinola Minovia, Arie; Asri Putri, Niken (Akuntansi & Ekonomika, 2023)
With the growing demand from stakeholders for published information, sustainability reporting and intellectual capital become the most critical issues in the business. Therefore, this study examines the effect of SR and IC on 42 energy and basic material companies’ value during 2016-2020. The test results found that sustainability report increase firm value but intellectual capital doesn’t affect the firm value. The additional test found that the economic and social categories in the sustainability report increased firm value, surprisingly environment sector did not affect firm value. This research contributes to the government making regulations on the company’s sustainability report, especially the environment, and also contributes to the company giving more attention to the company’s intellectual capital, especially for energy and basic material companies.